KAJIAN HISTORIS DAN POLITIK KOREA SELATAN TERHADAP MUSLIM KOREA SELATAN - Hasanah, Rabiatul; Muhammad Irfan Wahid; Muhammad Husni (Jurnal Diskursus Islam, 2026)
This study aims to analyze the historical and political dynamics of the Muslim community in South Korea by highlighting the tension between Islamophobia and the state's inclusive policies. This study fills a research gap because previous studies tended to be partial and failed to comprehensively integrate historical, political, and social aspects. The method used was a qualitative one with a historical approach through literature review. The research findings indicate that although the state guarantees religious freedom and promotes Muslim-friendly policies, the Muslim community still faces discrimination and social marginalization. Under these conditions, the Muslim community develops adaptation strategies through identity strengthening, education, and interfaith dialogue. This study concludes that there is a tension between inclusive state policies and exclusive social realities, which drives the formation of cultural adaptation patterns and resistance within the Muslim community in the process of social integration